Technical and economic assessment of the pyrolysis and gasification integrated process for biomass conversion. (15th June 2018) - Im-orb, Karittha; Wiyaratn, Wisitsree; Arpornwichanop, Amornchai
Abstract: The technical and economic prospects for synthesis gas production via an integrated biomass pyrolysis and gasification (IBPG) process are evaluated for the case where rice straw is a considered feedstock. Modeling of the integrated process is performed by using the Aspen Custom Modeler program. The simulation results show that the production rates of synthesis gas and bio-oil derived from an IBPG process increase as pyrolysis temperature increases, due to the increased volatiles. Compared to a conventional biomass gasification, IBPG provides additional bio-oil as a valued by-product, releases less waste heat and offers higher energy efficiency at the same synthesis gas production rate. The IBPG process with a pyrolysis temperature of 700 °C shows the best technical performance. However, pinch analysis indicates that the IBPG process with a pyrolysis temperature of 400 °C or 500 °C and conventional biomass gasification is technically feasible; the optimum heat integration structures are achieved. The economic analysis, which considers only the reaction-related equipment, indicates that the IBPG process with a pyrolysis temperature of 500 °C offers synthesis gas and bio-oil production rates of 1.185 and 0.2044 kmol h −1, respectively, and an energy efficiency of 68.86% is most economically feasible. Highlights: The techno-economic analysis of IBPG process of rice straw feedstock is performed. Performance of the IBPG and conventional gasification is compared. The syngas and bio-oil production rates increase as pyrolysis temperature increases. The IBPG run at a pyrolysis temperature of 500 °C is the most feasible process.